Volcanoes & earthquakes - Knight, Linsay (Macdonald Young Books, 1995)
Discusses the causes of volcanoes and earthquakes, and their impact on the environment and human settlements. Also looks at some famous volcanoes and earthquakes. Suggested level: primary, intermediate, junior secondary.